Pilot Plant Objectives and Considerations for Evaluating the Waste Disposal of High Slimes Heavy Mineral Sand Deposits - N Ross; N Goldup (The Australasian Institute of Mining and Metallurgy, 2001)
In recent years the heavy mineral mining industry has started to look more closely at the feasibility of mining moderate to high slimes deposits. During the initial stages of orebody evaluation the primary purpose of the pilot plant is to produce heavy mineral concentrate for metallurgical evaluation. Hence, generally little consideration is given to the disposal of the waste material (slimes and tailings). This paper suggests additional, simple, low-cost, tests that can easily be incorporated into an initial pilot plant operation. With this data a more definitive evaluation of available waste disposal options can be made during the early stages of the project. Thus, permitting better project focus and utilisation of resources. These tests include free settling of slimes, natural slimes drying and consolidation (undrained and drained), tailings stacking angles, and particle size distributions of input and waste streams, etc. The objective and method of each test is summarised, together with its relevance to possible waste disposal options. The results of this preliminary testwork can later be used to expand upon and define further tests for the second phase of pilot plant operations, which will enable a more definitive evaluation of a proposed waste disposal solution.